PRESENÇA DE ANTIBIÓTICOS, CONSERVANTES E RECONSTITUINTES EM LEITE UHT E PASTEURIZADO - Frederico Teixeira Corrêa; Sérgio Augusto de Sousa Campos; Sandra Maria Pinto (Universidade do Estado do Rio de Janeiro, 2015)
Milk is highly consumed by the general population, within severalage groups. To ensure consumer health, it is crucial that this foodproduct is free of certain chemical substances. In order to assessthe presence of antibiotics, conservatives and restoratives, as wellas the physico-chemical quality of whole milk commercializedin the south of the state of Minas Gerais, Brazil, 11 UHT milkbrands and four different pasteurized milk brands were boughtin local supermarkets. The physico-chemical evaluation wasconducted according to official methods. Brands were subjectedto the following analysis: total solids content, fat content, crudeprotein content, ashes, carbohydrates, titratable acidity, density at15°C (g/ml), freezing point, analysis of the presence of antibiotics,chlorides, formol, hydrogen peroxide, starch, sucrose andhypochlorite. It was concluded that the majority of the samplescomplied with the quality and safety standards required by thelegislation, mainly the UHT milk brands, which were appropriatefor consumption.